Reduced emotion-generated frontolimbic functional connectivity in psychostimulant-free ADHD youth with and without familial risk for bipolar I disorder. - Li, Qian; Qin, Kun; Lei, Du; Li, Wenbin; Tallman, Maxwell J.; Patino, L. Rodrigo; Sweeney, John A.; Gong, Qiyong; Li, Fei; DelBello, Melissa P.; McNamara, Robert K. (European Child & Adolescent Psychiatry, 2026)
Although youth with attention-deficit/hyperactivity disorder (ADHD) and a family history of bipolar I disorder (BD) are at increased risk for developing BD, the underlying neurobiological mechanisms remain poorly understood. Aberrant ventrolateral prefrontal cortex (VLPFC) and amygdala (AMY) functional connectivity (FC) have been implicated in the pathophysiology of BD. This study compared VLPFC-AMY FC in psychostimulant-free ADHD youth with (high-risk, HR) and without (low-risk, LR) a BD family history, and healthy controls (HCs). Subjects received a magnetic resonance scan while performing a continuous performance task with emotional and neutral distractors. Generalized psychophysiological interaction analysis was used to assess VLPFC-AMY FC in response to unpleasant emotional stimuli and attentional targets. A total of 144 adolescents (46 HC, 50 LR, and 48 HR) were included. In response to unpleasant emotional stimuli, FC between right VLPFC and left AMY differed among groups. HR youth exhibited lower right VLPFC-left AMY FC compared with both LR and HC, and LR youth exhibited lower right VLPFC-left AMY FC compared with HC. There were no group differences in right VLPFC-left AMY FC in response to attentional distractors. ADHD in conjunction with BD family history is associated with blunted emotion-generated right VLPFC-left AMY FC compared with ADHD youth without a BD family history and healthy youth, and may represent a neurobiological feature associated with genetic vulnerability to BD.